2017
DOI: 10.1021/acs.energyfuels.6b02125
|View full text |Cite
|
Sign up to set email alerts
|

A Mini Pilot-Scale Flow Loop Experimental Study of Turbulent Flow Wax Deposition by Using a Natural Gas Condensate

Abstract: Wax deposition is one of the important flow assurance problems in oil and gas production for both offshore and onshore fields. In this study, we experimentally investigated the turbulent flow wax deposition phenomena under single-phase turbulent flow conditions. The experiments were conducted in a mini pilot-scale flow loop by using Garden Banks condensate from the Gulf of Mexico. Condensate velocities of 1.89, 2.83, 3.78, and 4.72 m/s and testing durations of 2.67 h (2 h, 40 m), 8 h, 16 h, and 24 h were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…In order to validate the numerical model, we consider the wax deposition data of Singh et al 22 . The authors conducted wax deposition experiments using a Garden Banks condensate as operating uid, circulated in turbulent ow conditions in a D = 16.5 mm internal diameter pipe.…”
Section: Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to validate the numerical model, we consider the wax deposition data of Singh et al 22 . The authors conducted wax deposition experiments using a Garden Banks condensate as operating uid, circulated in turbulent ow conditions in a D = 16.5 mm internal diameter pipe.…”
Section: Validationmentioning
confidence: 99%
“…63 No data are available for the remaining properties of the deposit, which are set equal to those of the crude oil, except for the viscosity µ d that will be subject of a parametric analysis. Singh et al 22 reported that the deposit critical carbon number (CCN) of the operating uid was ∼ 30 and considered the total fraction of alkanes with carbon number above 30 (n-C30+ fraction) as the wax fraction of the uid. Accordingly, in the numerical model we assume that the non-wax pseudo component with the crude oil ow rateṁ c because the more ecient heat convection at the wall leads to a higher wall temperature gradient.…”
Section: Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…[18,72] 4.4 | A model for deposit aging: shear deformation of a cubical cage A number of studies have reported that, with time and under shear stress, the incipient gel-like structure undergoes compositional changes through a process called deposit aging. [33,50,54,[75][76][77][78]93,[129][130][131][132][133] During deposit aging, the concentration of lighter paraffins in the deposit decreases with time and that of the heavier paraffins increases. Experimental results have shown that a harder deposit, with a lower fraction of the entrapped oil, is formed under higher shear rates.…”
Section: Modelling Of Pipeline Flow Shut-downmentioning
confidence: 99%